Evaluation of Quadruple Real-Time PCR Method to Detect Enterococci Carrying Vancomycin-Resistant Genes vanA, vanB, vanM in Rectal Swabs - He, Yuanhui; Ruan, Genjie; Hao, Hui; Xue, Feng; Zhu, Sainan; Xiao, Bingbing; Zheng, Bo (Frontiers in Medicine, 2020)
Purpose: To evaluate the sensitivity and accuracy of quadruple real-time PCR method for the detection of enterococci carrying vancomycin-resistant genes vanA, vanB, vanM in rectal swabs. Methods: Choosing PCR-sequencing of DNA extracted directly from rectal swabs as gold standard, the results of quadruple real-time PCR method and traditional method (screening culture combined PCR-sequencing method whose DNA extracted from single colony) were compared to gold standard. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of quadruple real-time PCR method and the traditional method were obtained. The time required for the three methods was calculated. Results: The results between gold standard and quadruple real-time PCR method were similar. Compared to traditional method, the quadruple real-time PCR method had much higher sensitivity, specificity, PPV, NPV, and consistency. Our study found that quadruple real-time PCR method is beneficial for detection of enterococci carrying vanM with vancomycin heteroresistance. The traditional method had high specificity and NPV, but its sensitivity and PPV were not so ideal. The time needed for gold standard is minimum 28 hours; quadruple real-time PCR method takes 2–3 hours while traditional method consumes minimum 72 hours. Conclusion: Quadruple real-time PCR method can provide a rapid and reliable result for the diagnosis of the patients with colonized vancomycin resistant enterococci. This new method is beneficial for the active screening, timely clinical treatment measures, epidemiological research and hospital monitoring of enterococci carrying vancomycin-resistant gene, especially for the enterococci with vancomycin heteroresistance carrying vanM.